Analisis Pengembangan Potensi Wisata Desa Gajah - Ardhana Januar Mahardhani; Afriza Zahroni; Edwin Dwi Hartanto; Amy Nurlitasari; Zuhana Ade Wirakusuma (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The existence of Gajah Village, Sambit District, Ponorogo Regency is one of the villages that can be developed in terms of natural tourism through the existence of the Puncak Kuik area. This paper will look at the analysis of the development of the tourism potential of Gajah Village through the actors in it. Research using qualitative methods with data collection methods are observation, interviews, and documentation, using interactive data analysis model. From the results of the research it is known that the model for developing the tourism potential of Gajah Village seen through the pentahelix model which consists of five actors namely government, community, academics, media, and the business world has not been realized optimally, the five actors have not been interconnected and collaborated so that the development of a tourist area Puncak Kuik has not been implemented optimally. The government is still very limited in its role in the development of this tourist area so that the business world is also not willing to enter the Puncak Kuik tourist area due to poor road access. Of the five actors, it is the community and the media that have a big role to play in developing the Puncak Kuik area through the potential that exists in it, the community with self-supporting funds and the media through news or social media many of which expose the existence of the Puncak Kuik tourist area as a new tourist spot in Ponorogo Regency.